Strategi Pemasaran Berbasis Portofolio Produk pada UMKM Kerupuk Menggunakan Matriks Boston Consulting Group (BCG) - Atima, Abdul Wahid K; Lahay, Idham Halid; Pratiwi, Monica (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
UMKM play an important role in the regional economy, but they often face limitations in marketing strategies and market expansion. This study aims to analyze the marketing strategy of Karupuk Tore UMKM in Muara Bone Village using the Boston Consulting Group (BCG) method. The research approach used is descriptive qualitative with data collection techniques through observation, interviews, and documentation. Analysis is carried out by examining the market growth rate and relative market share of the marketed crackers products. The results show that Karupuk Tore products fall into several quadrants of the BCG Matrix, illustrating differences in growth potential and sales contribution among product variants. Based on this analysis, the recommended marketing strategies include developing flagship products, optimizing distribution, and utilizing digital marketing to enhance the competitiveness of Karupuk Tore UMKM.